The efficacy and safety of first-line monotherapies in primary therapy of invasive aspergillosis: a systematic review - Chen, Yan; Zhao, Jiaojiao; Wang, Yifei; Ge, Long; Kwong, Joey Sum-wing; Lan, Junjie; Zhang, Rui; Zhao, Huaye; Hu, Linfang; Wang, Jiaxue; Sun, Shuimei; Tan, Songsong; et al. (Frontiers in Pharmacology, 2025)
ObjectiveSeveral antifungals are available for the treatment of patients with invasive aspergillosis (IA). This study aims to evaluate the relative efficacy and safety of the first-line monotherapies in primary therapy of IA through network meta-analysis (NMA).MethodsWe systematically searched PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, VIP database, Wanfang database, and China Biology Medicine for randomized controlled trials (RCTs) up to July 2023 that evaluated the efficacy and safety of monotherapies. We performed NMA with a frequentist random effects model and assessed the certainty of evidence using the GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach. Primary outcomes were the all-cause mortality at week 12, and secondary outcomes included overall response rate, and incidence of adverse events (AEs) and severe adverse events (SAEs).ResultsA total of three RCTs involving 1,368 participants (four antifungals) were included. The NMA showed that compared to amphotericin B deoxycholate (D-AmB), the triazoles (posaconazole (POS), isavuconazole (ISA) and voriconazole (VCZ)) can improve the overall response rate in primary therapy of IA, but only VCZ and ISA can reduce the all-cause mortality at week 12 for patients with proven and probable IA (VCZ vs D-AmB: RR = 0.66, 95%CI = 0.47–0.93, moderate certainty; ISA vs D-AmB: RR = 0.52, 95%CI = 0 .31–0.86, low certainty). ISA (SUCRA = 93.50%; mean rank, 1.20) seemed to be the most effective therapy in the above population. As to proven, probable, and possible IA patients, the triazoles were superior to D-AmB in terms of reducing all-cause mortality. Furthermore, the risk of AEs and SAEs was comparable for the three triazoles, but the risk of SAEs was significantly higher for D-AmB than others.ConclusionThe efficacy and safety of triazoles are more favorable than D-AmB in the primary therapy of IA, with ISA being the optimal choice.Systematic Review RegistrationPROSPERO CRD42023407632.